Observation of growth rate of catfish (Pangasius sp.) against mixed feed fermentation of mustard and cabbage waste flour - Yustina Yustina; Sri Wulandari; Oky Priawan (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2021)
A study was conducted to measure the growth rate of catfish (Pangasius sp.) due to feeding on a mixture of fermented mustard and cabbage waste flour (FMCWF). Catfish are distributed in each container per box, consisting of five fish with an initial weight of 3 – 5 grams. During 56 days of cultivation, three times a day were fed with a feeding rate of 5%. The randomized block design method was used as the concept of this research. There were five treatments and each treatment was repeated three times. The type of catfish feed provided consisted of factory feed and its mixture with different percentages of FMCWF: P0 (manufactured feed brand Matahari Sakti); P1 (FMCWF 15%); P2 (FMCWF 30%); P3 (FMCWF 45%); and P4 (FMCWF 60%). Observations were made on several parameters such as absolute weight growth, feed conversion ratio, and water quality. Based on the analysis of variance (ANOVA) test, the results showed that the growth rate of catfish was influenced by FMCWF with a significant effect (p < 0.05). The best growth rate was given to P2 treatment (FMCWF 30%) with an absolute weight growth of 8.11 grams and a feed conversion ratio of 1.5.